PELATIHAN INOVASI PRODUK DAN PEMASARAN UNTUK MENINGKATKAN MERK UMKM DI BANTEN - Surachman, Surachman; Triana, Leni; Kartika, Rika; Salapudin, Salapudin; Romli, Ombi; Sumarsid, Sumarsid; Octavitri, Yollanda (Yayasan Education and Social Center, 2023)
This community service activity aims to improve the brand of Micro, Small and Medium Enterprises (MSMEs) in the Banten region through product innovation and marketing training activities using the Zoom Meeting platform. The implementation method is carried out by combining online and interactive approaches to facilitate maximum participation from MSME actors in Banten. The training was carried out online via Zoom Meeting, allowing participants to participate without needing to be physically present, considering mobility constraints and health considerations that are still relevant. During the training session, practitioners and experts in the fields of product innovation and marketing were involved as resource persons, providing in-depth insights and sharing practical experiences. The evaluation results show an increase in participants' understanding and skills regarding product innovation and marketing. Apart from that, the implementation of marketing strategies obtained from the training also succeeded in improving the image and brand of MSMEs in Banten. Active participation in the Zoom Meeting session proved the effectiveness of the online implementation method in delivering material and facilitating discussions between participants. This community service activity makes a positive contribution to the development of MSMEs in Banten, strengthens the brand position of their products, and promotes the application of information technology as a means of increasing capacity. It is hoped that the implications of this community service activity can provide inspiration and guidance for similar efforts in developing MSMEs in other areas